MEMAHAMI TRANSISI PEMUDA PERBATASAN - Oki Rahadianto Sutopo (REFORMASI, 2016)
Abstract: This article presents an analysis of youth transition that lives in the borderland area. By using qualitative methods, the research found that during the process of transition, borderland youth had to negotiate with the structural obstacles especially the lack of basic facilities, such as electricity supply, road, education, and health. Furthermore, those structural obstacles as well as rapid social change had an impact for the pathways of borderland youth transition. There were three pathways from school to work transition: fast track transition, stay in the village and become a peasant or move to other area to work as a labor. However, the transitions of borderland youth were still facing the uncertainty in the future. The State had to give supports for borderland youth to eliminate structural obstacles by building some of the basic facilities in the village. Key words: transition; borderland youth; structural obstacles Abstrak: Artikel ini menjelaskan mengenai transisi pemuda dari daerah perbatasan. Dengan menggunakan metode kualitatif ditemukan bahwa dalam proses transisi, pemuda perbatasan mengalami hambatan-hambatan struktural terutama minimnya fasilitas dasar seperti listrik, jalan, pendidikan dan kesehatan. Hambatan struktural ini berdampak pada tiga rute transisi pemuda perbatasan menuju dunia kerja terutama paksaan untuk menempuh jalur cepat, menetap sebagai petani atau berpindah ke daerah lain sebagai buruh. Ketiga rute ini sama- sama menghadapkan pemuda perbatasan pada kondisi ketidakpastian mengenai masa depan. Sebagai solusi, Negara perlu hadir untuk mereduksi hambatan-hambatan struktural yang harus dijalani oleh pemuda perbatasan dengan membangun fasilitas-fasilitas dasar. Kata Kunci: transisi; pemuda perbatasan; hambatan struktural